Dosimetric Comparison Between Intensity Modulated Radiotherapy and Volumetric-Modulated Arc Therapy Radiotherapy in Hypofractionation Bladder Preservation - Abdel Maksoud Mostafa, Radwa; El Sebaei, Medhat; Saad Zaghloul, Mohamed; Abdel Karim, Shreif; Mohamed Abdelaziz, Dina (Journal of Neonatal Surgery, 2025)
ABSTRACT Objective: To compare the intensity-modulated radiotherapy (IMRT) 11-field technique to Volumetric-modulated arc therapy (VMAT) for bladder preservation hypofractionated radical radiotherapy in high-risk urothelial bladder cancer cases. Patients and Methods: A dosimetric analysis of 10 urothelial bladder cancer patients who underwent maximum transuretheralbaldder resection (TURBT) followed by bladder preservation using hypofractionation. These patients were presented to the radiotherapy department, National Cancer Institute, Cairo, between 2018 and 2020 with radical radiotherapy using the IMRT technique. Two plans were designed for each patient, one using 11-field IMRT and the second using Rapid arc. The two techniques were compared, including the PTV, bowel bag, rectum and both femoral heads, also treatment time. Results: Comparing different DVHs, the planning target volume (PTV) was adequately covered in both plans, while the 11-field IMRT technique delivered significantly lower monitor unit and treatment time and better homogeneity index and conformity index. Conclusion: The results of the comparison between IMRT and VMAT show that VMAT is superior to IMRT in terms of homogeneity and conformity and treatment time.